Molecular Detection of Virulence Genes in Candida albicans Isolated from Cow Milk: Deteksi Molekuler Gen Virulensi pada Candida albicans yang Diisolasi dari Susu Sapi - Aseel Razak Al-Rekaabi; Mahdi Saber Al-Deresawi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Milk and its derivatives are essential nutritional sources, but they can serve as vehicles for pathogenic microorganisms, including opportunistic yeasts like Candida albicans, which pose significant health risks. Specific Background: C. albicans is a commensal organism capable of transitioning into a pathogenic state, aided by virulence genes such as ALS1 and PLB1, which enhance adhesion and biofilm formation. Knowledge Gap: Despite its clinical relevance, limited molecular data exist on C. albicans virulence factors in raw cow milk from rural regions, where hygienic practices may be suboptimal. Aims: This study aimed to isolate C. albicans from cow milk and detect key virulence genes (ALS1 and PLB1) using PCR analysis. Results: Of 50 milk samples, 28% were positive for C. albicans; 92% of isolates formed biofilms, while ALS1 and PLB1 were detected in 85% and 100% of isolates, respectively. Novelty: This research provides the first molecular evidence of virulent C. albicans in cow milk from rural Wasit Province, emphasizing its zoonotic potential. Implications: The findings highlight the need for improved dairy hygiene, routine monitoring, and antifungal strategies targeting virulence factors to enhance milk safety and public health.Highlight : A total of 28% of cow milk samples were found to contain Candida albicans. The virulence genes PLB1 (100%) and ALS1 (85%) were successfully identified using PCR. The findings indicate that C. albicans in milk can pose health risks to consumers if not handled hygienically. Keywords : Candida Albicans, CALB1 Gene, ALS1 Gene, PLB1 Gene, PCR